Survival time of post and cores after recementation: A 16-year retrospective study with special focus on loss of retention. (December 2022) - Vogler, Jonas Adrian Helmut; Lehmann, Moritz; Schlenz, Maximillane Amelie; Zierden, Karina; Rehmann, Peter; Wöstmann, Bernd
Abstract: Objectives: Numerous studies investigating the survival time of post and cores have found that loss of retention is the most common cause of failure Nevertheless, investigations focusing on decementation, survival after recementation, and the influencing parameters in a large number of patients with long follow-up periods are lacking. Therefore, the aim of this short communication article is the survival analysis of post and cores after recementation and repeated loss of retention. Materials and Methods: During the observation period (2004–2020), 653 patients received 953 post and cores. From these, 112 post and cores which suffered loss of retention were selected. The patient files were analysed for the following parameters: Type of covering prosthetic restoration, location, type of tooth, luting material, post and core material, bone attachment and therapist. The survival time until loss of retention or repeated decementations after recementation was documented. Survival probability was assessed using Kaplan–Meier and Cox regression analyses. Results: The average time until decementation was 13.33 years. The cumulative decementation rate was 11.8%, while in 42.0% of the cases, post and cores showed multiple losses of retention. A significant influence (Kaplan–Meier analysis) was recorded for the type of covering prosthetic restoration, type of tooth, luting material, post and core material and bone attachment. The multifactorial survival analysis (Cox regression) showed a significant influence of patient's age and the type of covering prosthetic restoration. Conclusions: Once decementation occurs, recementation neither guarantees definitive fit nor necessarily predetermines repeated decementations. Clinical significance: Post and cores should be avoided under primary crown-retained removable partial dentures (RPD). If this treatment is inevitable, a continuous follow-up is necessary to check the denture for proper fit to the tissues to prevent overloading on the post and core.